2016
DOI: 10.1097/sap.0000000000000224
|View full text |Cite
|
Sign up to set email alerts
|

The Postauricular Helix-based Adipodermal-pedicle Turnover (PHAT) Flap

Abstract: The PHAT flap is an original single-stage procedure for anterior auricular defects located on the antihelix or scapha. The single-layer PHAT flap is indicated in purely skin defect. The triple-layer ePHAT flap includes two subcutaneous extensions which increase its thickness and is indicated to restore the ear contours when cartilage has been removed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Two types of partially deepithelialized tunneled postauricular advancement flaps to repair anterior auricle defects have been documented. A postauricular helix-based turnover flap with direct closure of the retroauricular sulcus was first described by Beustes-Stefanelli et al, 13 with a risk of overtucked ear because of constriction of the auricular sulcus. A tunneled flap elevated from the mastoid skin beyond the postauricular sulcus was reported by Cerejeira et al 14 A postauricular revolving-door island flap 6 was described for conchal anterior defect, and pedicle at the postauricular sulcus has been proposed for anterior defects of the antihelix and concha, with a less satisfying cosmetic result and an attached lobule.…”
Section: Discussionmentioning
confidence: 99%
“…Two types of partially deepithelialized tunneled postauricular advancement flaps to repair anterior auricle defects have been documented. A postauricular helix-based turnover flap with direct closure of the retroauricular sulcus was first described by Beustes-Stefanelli et al, 13 with a risk of overtucked ear because of constriction of the auricular sulcus. A tunneled flap elevated from the mastoid skin beyond the postauricular sulcus was reported by Cerejeira et al 14 A postauricular revolving-door island flap 6 was described for conchal anterior defect, and pedicle at the postauricular sulcus has been proposed for anterior defects of the antihelix and concha, with a less satisfying cosmetic result and an attached lobule.…”
Section: Discussionmentioning
confidence: 99%
“…Beusters-Stefanelli et al 3 reported a postauricular helix-based adipodermal pedicle turnover (PHAT) flap for defects of the antihelix, which is a local pedicled skin flap taken from the posterior surface of the ear. This is a single-stage technique with reliable vascular pedicle for antihelical defects but retroauricular sulcus loss and distortion of the ear shape can occur in cases with a large retroauricular donor site defect.…”
Section: Discussionmentioning
confidence: 99%
“…Hesitation to perform skin graft is inevitable when the bare cartilage is exposed. There has been little discussion in the literature regarding reconstructive techniques for antihelical defects, as compared to the helical area, as the helical part of the auricle is most often affected by skin cancers and trauma 2,3 . In this article, the authors introduce a surgical technique to reconstruct the antihelical auricular defect with exposed bare cartilage, using adipoperichondrial turnover flap from cephalic portion of the earlobe followed by full-thickness skin graft.…”
mentioning
confidence: 99%
“…A postauricular island flap with adipodermal pedicle was transferred to the defects in antihelix or scapha through the transauricular tunnel with a 180-degree turnover. 4 In summary, the postauricular or preauricular flap may be a good alternative for repairing small auricular tissue defects (< 2 cm in diameter) because of color similarity, the appropriate thickness, good vascularization, inconspicuous scar, and one-stage procedure.…”
Section: An Active Role Of Reconstructive Surgeon In Otologic Tumor S...mentioning
confidence: 99%